Effect of Anion Presence to Copper (II) Bromide Response Towards Anionic Surfactant in Water Sample - Ahmad Waliyuddin Nor Asri,; Nor Haslina Hashim, (Progress in Engineering Application and Technology, 2024)
Maintaining cleanliness in our daily lives involves the use of cleaning agents, often containing surface-active agents or surfactants, which play a crucial role in various industries. Despite their widespread use, the environmental impact of surfactants, specifically anionic surfactants, has raised concerns due to their poor biodegradability and various adverse on ecosystems. Previous research has shown that Copper (II) Bromide, CuBr2, could possess the potential to detect anionic surfactant in water sample. There is various factor that needs to be addressed before confirmation regarding the ability of CuBr2 to detect anionic surfactant can be determined. This is due to countless factor that may occur in real-life situation that may affect the credibility of this new proposed method.  Methylene Blue Active Substance (MBAS) method is the well establish technique that is used to detect anionic surfactant at the moment. However, this method is time-consuming and employs the use of toxic chemical which is chloroform to extract the solution. Therefore, this study aims to find out the ability of CuBr2 to detect anionic surfactant in presence of anion in the same water sample to anticipate one of the various scenario that may occur in real-life situation. This study comprises of laboratory investigation that uses SDS as the anionic surfactant, TEA as organic solvent and multiple anion samples which were chloride ion, nitrate ion and sulphate ion to observe the response of CuBr2 towards the presence of anion and anionic surfactant in the same water sample. A calibration curve was constructed with R2 value of 0.9752 and equation of   which was used to determine the final concentration of each SDS sample that was mixed with 4mM and 8mM of anion individually. The result shows that, the presence of anion in the water sample reduce the absorbance value of the sample. The mixing of SDS and anion in the sample form a metal complex resulting in CuBr2 unable to react with SDS in the sample. This indicates that CuBr2 can only directly detect anionic surfactant precisely as long as there is no other anion element in the water sample. It can be concluded that this method is non-selective towards anionic surfactant